On paper. - Gould Galleries (South Yarra [Vic.] : Gould Galleries, 2006)
Artists exhibited include David Larwill, Fred Williams, Sidney Nolan, Howard Arkley, Donald Friend, Brett Whiteley and Norman Lindsay.
Title from inside invitation.
Exhibition held at Gould Galleries until 17 December 2006.
Keywords: Art, Australian -- Victoria -- South Yarra -- Exhibitions